PENGARUH BRAND IMAGE DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH PADA MAHASISWI JURUSAN EKONOMI SYARIAH FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN PADANGSIDIMPUAN - Hamni Fadlilah Nasution (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Students from the Islamic Economics Department, Faculty of Economics and Islamic Business, IAIN Padangsidimpuan, must be careful in choosing choices from various cosmetic brands that have good quality and brand image. Female students must be able to distinguish cosmetic products that are officially labeled halal and unofficial halal labels from the Indonesian Ulema Council for consumption. The formulation of the problem from this study is whether brand image and halal label have a partial and simultaneous effect on wardah cosmetic purchasing decisions on Islamic economics students from the faculty of economics and Islamic business at IAIN Padangsidimpuan. The purpose of this study is to determine the effect of halal brand image and label partially and simultaneously on wardah cosmetic purchasing decisions on Islamic economics students from the faculty of economics and Islamic business at IAIN Padangsidimpuan. The discussion in this study relates to the field of marketing. In this connection the approach taken is theories relating to brand image, halal label and purchasing decisions and certain parts of the science. This research is a quantitative study that uses data calculations using statistical calculations with the help of SPSS version 22. Population in this study are all the number of students in Islamic economics majoring in Islamic Economics and Business IAIN at the level of 788 people and a sample of 89 people. Data analysis techniques are multiple linear regression, classic assumption test, coefficient of determination, t test and F test. The results of the research obtained partially have an effect on the brand image of cosmetic purchasing decisions as evidenced by the value of t count t table (4.497 1.663). For the halal label variable also has an influence on cosmetic purchasing decisions as evidenced by tcount t table (2.970 1.663). Based on the simultaneous results obtained by the value of Fcount Ftable (20.583 2.37), it can be concluded that there is a significant effect between the variable brand image and halal label on cosmetic purchasing decisions, with the coefficient of determination, the adjusted R2 value of 0.308 or 30, 8%, indicating the brand image and halal label variables influence purchasing decisions and the remaining 69.2% is influenced by other factors beyond the research conducted by the researcher. Keywords: Brand Image, Halal Label, and Purchasing Decision